Controls on the chemical composition of ferromanganese crusts from deep-water to the summit of the Rio Grande Rise, South Atlantic Ocean - Benites, Mariana; González Sanz, Francisco Javier; Hein, James R.; Marino, Egidio; Reyes Andrés, Jesús; Millo, Christian; Jovane, Luigi (Marine Geology, 2023)
[EN] Ferromanganese (FeMn) crusts at the summit of Rio Grande Rise (RGR) (625–850 m) in the southwest Atlantic Ocean show two contrasting generations, an older, typically thicker one, that is strongly phosphatized, and a younger thinner nonphosphatized crust. Here, we investigate for the first time a suite of deep-water FeMn crusts from RGR collected from depths of 1505–5060 m to evaluate the extent of phosphatization and the controls on the variations in chemical composition. We use a range of analytical techniques to study the mineralogy, chemical composition, and petrography of the crusts. Deep-water (>1500 m) RGR FeMn crusts are hydrogenetic, composed of vernadite and goethite with minor amounts of 10 Å manganates in a few samples. Aluminosilicates (feldspar, clay minerals) and quartz are important components of the crusts, especially below 4000 m. In general, crusts from below 2000 m have high contents of hydrogenetic metals (e.g., As, Be, Co, Cu, Mo, Sb, Se, Ti, Th, Tl, U, Zn, rare earth elements) and lack calcite and phosphate minerals, contrasting with crusts from the summit. The contents of Mn, Co, V, As, Ni, Mo, Tl, U, Zn, Sb, P, and Ca in crusts decrease from 2008 to 5218 m water depth due to biological productivity, the strength of the OMZ, and phase association. Besides, periods of increased paleoproductivity and intensified OMZ may have provided more metals related to biological activity (Mn, Co, Ni, V, As, Tl, P) to the shallower-water crusts. On the other hand, Si, Al, K, Cu, and Th contents increase with water depth and reflect entrained detrital material, the characteristic dissolved Cu seawater profile, and the presence of the silicate-rich AABW. The Fe content and growth rates are mainly influenced by the oxygenation of water masses (NADW and AABW) and the input of detrital material. Subsidence probably played a role in the temporal decrease in contents of Mn and Co and increase in Al, Si, and growth rates in crust D20–1, due to increasing distance from the OMZ and enhanced detrital input. ...